التمويل الإسلامي للمؤسسات الصغيرة والمتوسطة: دراسة حالة الجزائر - ضحاك، نجية; قرومي، حميد (الهيئة العالمية للتسويق الإسلامي, 2021)
بات موضوع تمويل المشاريع والتي نعبر عنها في الجزائر بالمؤسسات الصغيرة والمتوسطة موضوع الساعة، وإنه من نجاحات هذا النوع من المؤسسات والذي يشكل النسيج الاقتصادي هو موضوع تمويلها. لقد قمنا في هذا البحث بتعريف المؤسسات الصغيرة والمتوسطة حسب القانون الجزائري، ثم قدمنا خصائصها وأشكالها، وكبديل اقترحنا التعامل بالصيغ التمويلية الإسلامية في البنوك الإسلامية في الجزائر، وكذا محاولة معرفة واقع التمويل الإسلامي لهذه المؤسسات، وفي الأخير توصل البحث إلى جملة من النتائج أهمها ما يلي: - تطور المؤسسات الصغيرة والمتوسطة في الجزائر بشكل ملحوظ ؛ - التحكم في التمويل البنكي والعلاقة بين البنك و المؤسسات الصغيرة والمتوسطة؛ - عدم وجود سوق مالي والذي يجعل هذا النوع من المؤسسات تعترض للمخاطر المالية؛ - معظم القروض لتمويل هذا النوع من المؤسسات يطغى عليه التمويل التقليدي أي نظام التمويل باستعمال الفائدة؛ - إن بنك البركة الجزائري لا يساهم كثيرا في تمويل المؤسسات الصغيرة والمتوسطة رغم وجود عدد معتبر من طلبيات القرض.
The issue of project financing, which we express in Algeria in small and medium enterprises, has become the topic of the hour, and it is one of the successes of this type of enterprise, which forms the economic fabric, is the subject of its financing. In this research we have defined small and medium size enterprises according to the Algerian law, then we presented their characteristics and forms, and as an alternative we suggested dealing with Islamic financing formulas in Islamic banks in Algeria, as well as trying to know the reality of Islamic finance for these institutions, and in the end the research reached a set of results, the most important of which are the following: - The development of small and medium enterprises in Algeria significantly; - Control of bank financing and the relationship between the bank and small and medium enterprises; - The absence of a financial market, which makes this type of institutions vulnerable to financial risks; - Most of the loans to finance this type of institution are dominated by conventional financing, i.e. the interest-based financing system. Al Baraka Bank of Algeria does not contribute much to financing small and medium enterprises, despite the presence of a significant number of loan requests.
Keywords: التمويل الإسلامي -- المؤسسات الصغيرة -- المؤسسات المتوسطة -- الجزائر -- المجتمع الجزائري